Water for the Erbil Plain: the relationship between water supply and settlement from the Neo-Assyrian to the Seleucid Period (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
This paper analyzes the relationship between the water supply system and changes in settlement patterns in the Erbil Plain (Kurdistan Region of Iraq) from the Neo-Assyrian period (late 10th–late 7th century BCE) to the Seleucid period (late 4th–mid 2nd century BCE). Recent excavations and extensive survey projects in the region have shown that the collapse of the Neo-Assyrian system, leading to the abandonment of imperial infrastructure, resulted in significant changes in the exploitation of the Erbil Plain and a reduction in the number of settlements in what had once been the rural heartland of the empire. Evidence of a recovery in settlement activity and a territorial reorganization becomes apparent starting from the Hellenistic period, marked by the Seleucid kingdom's renewed interest in this region, which served as an important communication corridor between the Tigris River to the west and the Zagros Mountains to the east.
Keywords: Erbil Plain; Settlements; Water Supply; Landscape; Neo-Assyrian Period; Post-Assyrian Period; Hellenistic Period